Improving detection of undiagnosed HIV through routine screening in a central London emergency department. Issue 4 (5th December 2022) - Fox, Matilda; Pettit, Rosie; Mutengesa, Ernest; Harper, Alice; Nakhoul, Maria
Abstract : HIV is a global public health issue. Routine testing for HIV should be performed on all 16–59 years old attending emergency departments (EDs) in high-prevalence areas in the UK. In August 2020, Charing Cross Hospital ED, situated in an 'extremely high-prevalence' area, had no formal guidelines on HIV testing. We aimed to increase HIV testing in 16–59 years old attending our ED to 25% by August 2021 through a quality improvement project, based on the Methodology for Improvement Model, performing six Plan–Do–Study–Act cycles over a 12-month period. An initial ED staff survey revealed 55% (n=22/40) of respondents were unsure of national HIV testing guidelines. Barriers to good testing practice included: lack of clarity on protocols for consent and indication, cost and perceived stigmatisation of patient groups. Interventions were employed at regular intervals, including employment of an HIV nurse advocate, inclusion of HIV tests in a blood test careset during ED triage, and updated trust guidelines that reflect national guidelines. Overall, we did achieve our original 12 month aim, with an average testing rate of 28% of our target group between September 2020 and August 2021. Extending the project to January 2022 has resulted in continued improvements in monthly testing rates, reaching 44% in December 2021. Further analysis revealed interventions led to a statistically significant and sustained increase in monthly testing rates on seven occasions. Valuable lessons were learnt in sustaining improvements in a busy department, changing long-held beliefs regarding consent for testing, and education around HIV care in the UK. Project write-up was formatted using the Revised Standards for Quality Improvement Reporting Excellence (SQUIRE) template.